THE INFLUENCE OF LEVERAGE AND PROFITABILITY ON COMPANY VALUE WITH COMPANY SIZE AS MODERATING VARIABLES (STUDY ON COMPANIES MANUFACTURING AUTOMOTIVE INDUSTRY SUBSECTOR YEAR 2014-2019) - Sefril Sefril; M Firza Alpi (Proceeding International Seminar of Islamic Studies, 2022)
This study was conducted with the aim of examining and analyzing the effect of leverage and profitability on firm value moderated by company size in automotive companies listed on the Indonesia Stock Exchange, either directly or indirectly. The population in this study were all automotive companies listed on the Indonesia Stock Exchange, while the samples that met the sampling criteria were observations made for six years and as many as seven automotive companies listed on the Indonesia Stock Exchange. This research approach uses causal research. Data collection techniques in this study using documentation techniques. and the analysis technique used is path analysis, hypothesis testing and the coefficient of determination using Partial Least Square (PLS) version 3.00 software.